A Comparison of p-median and Maximal Coverage Location Models with Q–coverage Requirement. (2016) - Karatas, Mumtaz; Razi, Nasuh; Tozan, Hakan
Abstract: A facility location problem considers locating a certain number of facilities with the objective of finding their best locations. For most real life situations, it is more realistic to consider the requirement of satisfying a demand with multiple facilities in order to ensure a backup supply. The back-up supply is necessary especially for public or emergency service location problems where a covered demand may not be serviced if its designated facility is engaged serving other demands. Moreover, this issue is more likely to occur when the number of demand locations is much higher. In this study we consider two classic location models, the p -median and maximal coverage location, and compare their performances with respect to five decision criteria under Q -coverage requirement. For this purpose we generate random problem instances and solve each instance with both models for different Q -coverage values. Our comparisons reveal the tradeoffs in selecting the location model for a given problem when the decision maker assesses the performance with multiple criteria.